External validation of an algorithm to personalize nerve sparing approaches during robot-assisted radical prostatectomy in men with unilateral high-risk prostate cancer - Rodriguez-Sanchez, Lara; Martini, Alberto; Zhuang, Junlong; Guo, Hongqiao; Rajwa, Pawel; Mandoorah, Qusay; Haiquel, Luciano; Shariat, Shahrokh F; Gandaglia, Giorgio; Valerio, Massimo; Marra, Giancarlo; Young Academic Urologists Working Group on Prostate Cancer of the European Association of Urology (Prostate cancer and prostatic diseases, 2025)
Limited evidence exists about preserving neurovascular bundles during radical prostatectomy (RP) for high-risk prostate cancer (HRPCa) patients. Hence, we validated an existing algorithm predicting contralateral extraprostatic extension (cEPE) risk in unilateral high-risk cases. This algorithm aims to assist in determining the suitability of unilateral nerve-sparing RP. Among 264 patients, 48 (18%) had cEPE. The risk of cECE varied: 8%, 17.2%, and 30.8% for the low, intermediate, and high-risk groups, respectively. Despite a higher risk of cECE among individuals classified as low-risk in the development group compared to the validation group, our algorithm's superiority over always/never nerve-sparing RP was reaffirmed by decision curve analysis. Therefore, we conclude that bilateral excision may not always be justified in men with unilateral HRPCa. Instead, decisions can be based on our suggested nomogram.
Keywords: Nomograms; roboticky asistované výkony; Prostatic Neoplasms; léčba šetřící orgány; prostata; nádory prostaty; Humans; Algorithms; lidé středního věku; Organ Sparing Treatments; Precision Medicine; Aged; senioři; lidé; individualizovaná medicína; nomogramy; Prostatectomy; Robotic Surgical Procedures; Male; Prostate; Middle Aged; algoritmy; prostatektomie; Risk Assessment; mužské pohlaví; hodnocení rizik